Shear bond strength fatigue limit of rest seats made with dental restoratives - Lopes, José Fernando Scarelli; Vergani, Carlos Eduardo [UNESP]; Giampaolo, Eunice Teresinha [UNESP]; Pavarina, Ana Claudia [UNESP]; Machado, Ana Lucia [UNESP] (My University, 2007)
Purpose: This study compared the shear bond strength (SBS) to enamel of rest seats made with a glass-ionomer cement (Fuji IX GP Fast), a resin-modified glass-ionomer cement (Fuji II LC), and a composite resin (Z100 MP) under monotonic and cyclic loading. Materials and Methods: Rest seats were built up onto the lingual surfaces of 80 intact human mandibular incisors. Specimens (n=10) were stored in distilled water at 37°C for 30 days and subjected to shear forces in a universal testing machine (0.5 mm/min) until fracture. The SBS values were calculated (MPa) using the bonding area (9.62 mm2) delimited by adhesive tags. A staircase approach was used to determine the SBS fatigue limit of each material. Specimens were submitted to either 10,000 cycles (5 Hz) or until specimen fracture. A minimum of 15 specimens was tested for each material. Scanning electron microscopy was used to examine the mode of failure. Data were statistically analyzed with one-way ANOVA and Tukey HSD tests (α = 0.05). Results: Z100 MP yielded higher (p < 0.05) SBS (12.25 MPa) than Fuji IX GP Fast (7.21 MPa). No differences were found between Fuji II LC (10.29 MPa) and the other two materials (p > 0.05). Fuji II LC (6.54 MPa) and Z100 MP (6.26 MPa) had a similar SBS limit. Fuji IX GP Fast promoted the lowest (p < 0.05) SBS fatigue limit (2.33 MPa). All samples showed cohesive failure patterns. Conclusion: Fatigue testing can provide a better means of estimating the performance of rest seats made with dental restoratives.
Keywords: Composite resins; Dental bonding; Fatigue; Glass-ionomer cements; Shear bond strength; Fuji II LC cement; Fuji IX GP Fast; glass ionomer; resin; silicon dioxide; unclassified drug; Z100 composite resin; zirconium; analysis of variance; comparative study; dental bonding; dental care; denture; enamel; human; incisor; materials testing; shear strength; Analysis of Variance; Composite Resins; Dental Abutments; Dental Bonding; Dental Enamel; Dental Stress Analysis; Denture Retention; Denture, Partial, Removable; Glass Ionomer Cements; Humans; Incisor; Materials Testing; Resins, Synthetic; Shear Strength; Silicon Dioxide; Zirconium